Impact of type 2 diabetes mellitus on low-grade inflammation in patients with ST-elevated myocardial infarction - M.V. Bielinskyi; N.M. Seredyuk; A.I. Vytryhovskiy; V.D. Koroliuk (Medičnì Perspektivi)
Chronic low-grade inflammation has emerged as a hallmark of type 2 diabetes mellitus (T2DM), contributing significantly to the pathogenesis of various cardiovascular diseases, notably ST-elevated myocardial infarction (STEMI). The intricate interplay between inflammation and cardiovascular health in the context of T2DM has been a subject of intensive research in recent years. In particular, the development of various markers of inflammation has provided valuable tools for better understanding the complex relationship between low-grade inflammation and cardiovascular disease in T2DM. Elevated levels of these markers have been consistently associated with increased cardiovascular risk in patients with T2DM, indicating their potential as prognostic indicators. The aim of the study was to investigate the potential association between type 2 diabetes mellitus and low-grade inflammation markers in patients with ST-elevated myocardial infarction through a comparative analysis of systemic immune-inflammation indices, fibronectin, and soluble suppression of tumorogenesis-2 (sST2) levels in ST-elevated myocardial infarction patients with and without type 2 diabetes mellitus. We enrolled 158 patients diagnosed with STEMI who were admitted to the Ivano-Frankivsk Regional Clinical Cardiological Center. The study population was divided into three groups: 1 – consisting of 45 patients with both STEMI and T2DM, and the 2 – consisting of 34 patients with STEMI only, T2DM only group – 69 patients, Control group – 10 healthy patients. In summary, the findings from the study provide compelling evidence to support the notion that patients who suffer from both STEM and T2DM exhibit a more robust inflammatory response and higher platelet count, compared to those with STEMI alone. These results suggest that the presence of T2DM may exacerbate the pro-inflammatory and pro-thrombotic state that is typically associated with STEMI, thereby emphasizing the critical need for early intervention to prevent or mitigate inflammation and platelet activation in this particular patient population. Type 2 diabetes mellitus patients with ST-segment elevation myocardial infarction show higher levels of inflammation markers and fibronectin, indicating greater low-grade inflammation. Elevated levels of soluble suppression of tumorigenicity 2 suggest myocardial remodeling. Targeting low-grade inflammation could be a potential therapy for STEMI in T2DM patients.